Optimization of different superplasticizer dosage for MSW gasification slag concrete - Aye, Zaw Win (Nanyang Technological University, 2022)
This project serves to explore the use and optimization of superplasticizers for municipal solid waste (MSW) gasification slag concrete for building purposes. Two common types of superplasticizers – Polycarboxylate ether (PCE) and Naphthalene sulfonate formaldehyde (SNF) were used to analyze the effects on the compressive strength and workability of the MSW gasified slag concrete. In total, 22 mixed samples were designed for this study, which includes 7 Control samples, 4 PCE-based samples, 4 SNF-based samples, and 7 mixed SNF-PCE samples. All 22 samples were tested for the workability through slump loss and compressive strength test at 28-days of air curing. A comparison of TGA analysis and TOC leaching will also be done across a control, PCE and SNF sample. The samples with the superplasticizers produced satisfactory results with higher workability and compressive strength as compared to the control samples. The effective range of % admixture to cement mass for each superplasticizer was also obtained. For the SNF-PCE sample, the optimum proportion was when the sample had a composite of 50% PCE or more. Lowering the PCE proportion resulted in lower workability and compressive strength as compared to a 100% SNF sample. The leachate analysis of TOC for each mix containing admixture was higher as compared to the control sample. However, the result is based on a 1-day leaching test. The expected leachate for TOC is expected to fall rapidly as the number of days progresses. Overall, the results suggest that the use of superplasticizers is highly recommended. The optimum % admixture and proportion can be obtained in the following study. Nevertheless, further studies and investigations would have to be conducted by adjusting the parameters such as the cement to slag ratio and curing days to achieve a complete reference guide on optimizing the admixture.